Risk Management for 4-H Youth Development Work: Risk Management Checklist - Dale Pracht; Paula M. Davis; Stefanie Prevatt; Janet Psikogios; Sarah Hensley (EDIS)
This is one publication in the series Risk Management for 4-H Youth Development Work. This series is intended to prepare UF/IFAS Extension county faculty, staff, volunteers, and youth to satisfactorily complete the important task of providing best practices in risk management strategies. This 4-page document provides a checklist that will help during 4-H event and activity planning. Written by Dale Pracht, Paula Davis, Stefanie Prevatt, Janet Psikogios, and Sarah Hensley and published by the UF/IFAS 4-H Youth Development Department, March 2018. http://edis.ifas.ufl.edu/4h384